Criminalidad organizada transnacional en Asia-Pacífico: repercusiones para la seguridad regional e internacional - Sansó-Rubert Pascual, Daniel (UNISCI Discussion Papers, 2011)
Asia-Pacific is an area of increasing strategic importance for international security, characterized by the multiplicity of actors with divergent objectives and by the multiform nature of the present challenges. However, it is the common and insidious threat of transnational organized crime must be emphasized. A variety of criminal groups and markets can be identified throughout Asia-Pacific, and Asian organized crime does not form a monolithic phenomenon; rather, it displays a polyhedral, complex and multidimensional landscape, with important regional manifestations and increasing international projection. Altogether, organized crime in the region currently represents one of the great challenges in terms of proliferation and expansion to other countries.